Technical and economic appraisal for harnessing a proposed hybrid energy system nexus for power generation and CO2 mitigation in Cross River State, Nigeria - Samuel Oliver Effiom; Precious Chibuzo O Effiom; Raymond Akwagiobe; Patrick O Odu (ASCEE, 2023)
By creating hybrid energy systems and obtaining a framework that equally satisfies a continuous operation for renewable energy technology, this study presents renewable and sustainable energy options as an integral method to energy transitioning from non-renewable to renewable energy utilization in Cross River State, Nigeria. For a needed load of 2424.25 kWh/day in Cross River State, this study focused on proposing a designed hybrid energy system (HES) nexus, mitigating CO2, and appraisal of the technical and economic viability. To accomplish this, HOMER software was utilized in simulating the ideal components that suggested a HES nexus. The software enabled the selection of the optimal HES using various renewable energy sources since it predicts future electrical demand, wind speed, solar irradiation, and temperature. Economic results obtained showed that the proposed HES's Levelized cost of energy (LCOE), net present cost (NPC), and operating cost (OC) were 0.89/kWh, 10,138,702 and 134,084.37 respectively. Further technical appraisal showed that the renewable energy conversion systems (RECs) make up 78.74% of the proposed HES. The photovoltaic (PV) arrays were primarily responsible for the hybrid energy system's electricity output. The annual electrical energy output was 1,984,111kWh (89.4%), produced by the PV arrays. The generic fuel cell produced the least, at 29,957kWh/year, accounting for just 1.35% of the total electricity produced. However, the wind power plant produced 205,365kWh/year annually. Furthermore, comparing the HES with diesel-powered generators, the system achieves a net-zero carbon emission status. Therefore, it has proven to be the most reliable energy as it will solve the problem of energy demand and reduces carbon emissions in Cross River State, Nigeria